Results of REXUS12's Suaineadh experiment: deployment of a spinning space web in micro gravity conditions - Sinn, Thomas; McRobb, Malcolm; Wujek, Adam; Skogby, Jerker; Rogberg, Fredrik; Wang, Junyi; Vasile, Massimiliano; Tibert, Gunnar (2012)
On the 19th of March 2012, the Suaineadh experiment was launched onboard the sounding rocket REXUS12 (Rocket Experiments for University Students) from the Swedish launch base ESRANGE in Kiruna. The Suaineadh experiment served as a technology demonstrator for a space web deployed by a spinning assembly. The deployment of this web is a stepping stone for the development of ever larger structures in space. Such a structure could serve as a substructure for solar arrays, transmitters and/or antennas. The team was comprised of students from the University of Strathclyde (Glasgow, UK), the University of Glasgow (Glasgow, UK) and the Royal Institute of Technology (Stockholm, Sweden), designing, manufacturing and testing the experiment over the past 24 months. Following launch, the experiment was ejected from the ejection barrel located within the nosecone of the rocket. Centrifugal forces acting upon the space webs spinning assembly were used to stabilise the experiment’s platform. A specifically designed spinning reaction wheel, with an active control method, was used. Once the experiment’s motion was controlled, a 2 m by 2 m space web is released. Four daughter sections situated in the corners of the square web served as masses to stabilise the web due to the centrifugal forces acting on them. The four daughter sections contained inertial measurement units (IMUs). Each IMU provided acceleration and velocity measurements in all three directions. Through this, the positions of the four corners could be found through integration with respect to known time of the accelerations and rotations. Furthermore, four cameras mounted on the central hub section captured high resolution imagery of the deployment process. After the launch of REXUS12, the recovery helicopter was unable to locate the ejected experiment, but 22 pictures were received over the wireless connection between the experiment and the rocket. The last received picture was taken at the commencement of web deployment. Inspection of these pictures allowed the ...